Pengaruh Persepsi Manfaat dan Kemudahan Penggunaan Terhadap Minat Menggunakan Dompet Digital OVO - Atriani, Atriani; Permadi, Lalu Adi; Rinuastuti, Baiq Handayani (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2020)
This study aims to determine the effect of the effect of perceived benefits and ease of use on the interest in using an OVO digital wallet. This type of research is associative research using survey sample data collection methods and nonprobability sampling techniques. The number of samples used in this study were 100 respondents. Data analysis method used is multiple linear regression analysis and goodness of fit test (t test, f test andÃ‚Â  ). The results showed the variable Perception of Benefits and Ease of Use had a positive and significant effect on Interest in Using OVO Digital Wallets. This is evidenced by the positive relationship between the variables of Perception of Benefits and Ease of Use which are factors driving interest. In addition to the benefits and ease of display on the features are also very influential because by beautifying or beautifying the appearance of features consumers will feel happy when making payment transactions using an OVO digital wallet. In addition to displaying the company's features, it must also be more aggressive in providing various kinds of promos, discounts and free vouchers that can attract consumers to use the OVO digital wallet application.